ANALISIS FRAMING PEMBERITAAN KEBIJAKAN EFISIENSI ANGGARAN OLEH PRESIDEN PRABOWO PADA MEDIA KUMPARAN.COM DAN KOMPAS.COM - VIOLINIDYA BR BARUS, RANDY SEKAR; Cindoswari, Ageng Rara (Commed Jurnal Komunikasi dan Media, 2025)
This study aims to analyze how online media outlets Kumparan.com and Kompas.com frame news coverage of President Prabowo Subianto's budget efficiency policy. The method used is Robert N. Entman's framing analysis model, which encompasses four main elements: define problem, diagnose causes, make a moral judgment, and suggest solutions. The results show that Kumparan.com consistently defines the issue of budget efficiency policy as a serious problem that has the potential to compromise public interests. The main issue raised is the threat to the quality and continuity of public services in vital sectors such as education, health, and regional infrastructure. Meanwhile, Kompas defines budget efficiency as a fiscal challenge that must be implemented carefully because the main issue of efficiency is its impact on the quality of public services, particularly in the education, health, and regional infrastructure sectors. However, Kompas does not display a crisis or conflict-like style of language, but instead chooses to highlight the difference between targeted budget efficiency and misdirected efficiency. This difference in framing demonstrates how media editorial positions can influence the way the public understands and evaluates government policies.